Dynamics of energy transfer and frequency upconversion in Tm3+ doped fluoroindate glass - Jerez, Vladimir A.; Araújo, Cid B. de; Messaddeq, Younes [UNESP] (AIP Publishing, 2004)
The spectroscopic properties of Tm3+-doped fluoroindate glasses (FIG) were described by single wavelength pumping in the red region. The Judd-Ofelt (J-O) theory was used to obtain the quantum efficiency of the 4f-4f transitions and other spectroscopic parameters. The dynamics of the fluorescence was investigated and energy transfer (ET) processes among Tm3+ ions were studied. The results indicate that a two-step one-photon absorption process is responsible for the ultraviolet upconversion (UC) emissions, and dipole-dipole interaction provides the main contribution for ET rate is equal to the decay rate of noninteracting among active ions.
Keywords: Absorption spectroscopy; Concentration (process); Doping (additives); Energy transfer; Fluorescence; Optical frequency conversion; Optical pumping; Positive ions; Quantum efficiency; Thulium; Dipole-dipole interactions; Excitation sources; Fluoroindate glasses (FIG); Wavelength pumping; Optical glass